(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Human resource management is intended to help organizations to address the issues of their employees in the most ideal way they would so be able to that organization objectives can be advanced. We can likewise say that SHRM is really overseeing individuals proactively on the grounds that it requires planning routes for an organization to address the issues of its employees, thinking ahead, and furthermore helping the employees to address the issues of the organization.